(3hUjI GdfHi (B( (3Udi Gddg Ydjg hSde (B)s
(3ChdgG (B:s
(3bGd MHjHi QShd Gddg (B( (3U(B) : (3jG Ydi EjGc hGdfejeI , aEf Gddg YR hLd deG Ndb hNdb GdLfI bGd dgG s
(3BNQgG (B:s
(3jG Ydi EMaX hUjJi ceG MaXJgG ef LHQjd (B( (3U(B) (3JeJ GdhUjI hJdG Pdc OYGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs